PENGARUH METODE DAN KEMAMPUAN MOTORIK TERHADAP KETERAMPILAN JURUS TUNGGAL PENCAK SILAT - Zainul Johor (Jurnal MensSana, 2019)
Looking at the learning outcomes data obtained by FIK UNP students who took basic martial arts courses from 1380 students, as many as 402 people (29.13%) who did not graduate and delayed scores were 278 (20.14%). That is, most students fail in basic pencak silat lectures. The purpose of this study was to see this study in general aiming to determine the differences in the results of learning methods and motor skills on the skills of a single stance Pencak Silat FIK UNP students in Padang. This type of research is Comparative. The research method used was an experiment with a 2 x 2 factorial design. As a population were all students of sports education study programs who took the basic martial arts courses at FIK UNP. The random sampling technique so that the sample in this study were 132 male students. The pencak silat single skill skill test uses the standard single test from IPSI. Tests of motor skills are used for the 40 m run test, throwing the ball into the wall, Shuttle run, throwing medicine balls, stand test strokes, and repeated flexibility for 20 seconds. Testing the hypothesis of this study uses two-way analysis of variance (ANAVA) techniques. Based on the analysis, it was found that Inquiry Methods were more effective in improving students' skills in the Single Pencak Silat Skill than the command method. There was an interaction between the method with Motorized Skill and the improvement of the student's Single Pencak Silat Skill. At a high level of Motor Capability, Inquiry methods are more effective than the command method for improving student Single Pencak Silat Skills. At a low Motor Capability level, the Command method is more effective than the Inkuri method for improving students' Single Skill Pencak Silat skills